(untitled) (Research, Society and Development, 2022)
The development of ecofriendly packaging, using renewable sources with a short life cycle, such as starch and chitosan, are highlighted in research as technological innovation. In the same sense, liquid whey (residue from the dairy industry) as a solvent (dispersing agent) in obtaining flexible films. The present work aimed to develop films of the starch blend with different concentrations of chitosan, solubilized in liquid whey by the discontinuous casting method. The films were characterized in terms of optical properties (colorimetry, opacity and transparency) and barrier to ultraviolet (UV) radiation. All films of the blends showed a total color difference (ΔE) visible in all treatments, ΔE >12. As well as good UV light radiation barrier property. The treatment with 25% (m/m) of chitosan presented a greater barrier to UV light (200 to 315 nm), region of greater susceptibility to lipid oxidation reactions in foods. Therefore, the whey presented a solvent-dispersing action in the formation of biopolymeric films. Thus, the hydrocolloid films showed a strong technological potential for use and application as ecofriendly packaging for application in dairy products rich in photo-oxidative compounds.